Diabetes and Prediabetes in Children With Cystic Fibrosis: A Systematic Review of the Literature and Recommendations of the Italian Society for Pediatric Endocrinology and Diabetes (ISPED) - Mozzillo, Enza; Franceschi, Roberto; Piona, Claudia; Passanisi, Stefano; Casertano, Alberto; Pjetraj, Dorina; Maltoni, Giulio; Calcaterra, Valeria; Cauvin, Vittoria; Cherubini, Valentino; D’Annunzio, Giuseppe; Franzese, Adriana; et al. (Frontiers in Endocrinology, 2021)
Cystic fibrosis related diabetes (CFRD) is a comorbidity of cystic fibrosis (CF) that negatively impacts on its clinical course. Prediabetes is an important predictor of either CFRD development and unfavorable prognosis of CF in both pediatric and adult patients. International guidelines recommend insulin only in case of CFRD diagnosis. Whether early detection and treatment of prediabetes may contribute to improve the clinical course of CF is still debated. A subgroup of pediatric diabetologists of the Italian Society for Pediatric Endocrinology and Diabetology (ISPED) performed a systematic review of the literature based on predefined outcomes: impact of pre-diabetes on clinical outcomes and on the risk of developing CFRD; diagnosis of diabetes and pre-diabetes under 10 years of age; effectiveness of therapy on glycemic control, impact of therapy on pulmonary function and nutritional status. Thirty-one papers were selected for the analysis data presented in these papers were reported in tables sorted by outcomes, including comprehensive evidence grading according to the GRADE approach. Following the grading of the quality of the evidence, the entire ISPED diabetes study group achieved consensus for the Italian recommendations based on both evidence and clinical experience. We concluded that in patients with CF, prediabetes should be carefully considered as it can evolve into CFRD. In patients with CF and prediabetic conditions, after complete evaluation of the OGTT trend, glucometrics, glycemic values measured during pulmonary exacerbations and/or steroid therapy, early initiation of insulin therapy could have beneficial effects on clinical outcomes of patients with CF and prediabetes.